PENGARUH KOMUNIKASI ELECTRONIC WORD OF MOUTH DAN CELEBRITY ENDORSER TERHADAP BRAND AWARENESS KONSUMEN BEAUTYHAUL - Rahma, Adinda Namira; Afriani, Anindita Lintangdesi (Transpublika Publisher, 2025)
Online shopping is currently in great demand by the public, especially for skincare and cosmetic products. With the presence of beauty e-commerce, it makes easier for people to find beauty products. There are several beauty e-commerce companies that have emerged in Indonesia, one of them is BeautyHaul. BeautyHaul is also the first beauty e-commerce presence in Indonesia. With competition between e- commerce, it is important for BeautyHaul to identify what factors can form brand awareness among the public. The factor that forms brand awareness is the use of marketing communications, one of them is electronic word of mouth. In addition, other factors that can form brand awareness by using celebrity endorsers. This study aims to determine the effect of electronic word of mouth communication and celebrity endorsers on brand awareness among BeautyHaul consumers in Indonesia. The research method used quantitative with convenience sampling technique. The population of this research is visitors to the BeautyHaul website in the fourth quarter of 2022. Then, the data was processed using the SPSS application statistical method with multiple linear regression tests. The results showed that 1) electronic word of mouth has an effect on brand awareness; 2) Celebrity endorsers have an effect on brand awareness; and 3) Electronic word of mouth and celebrity endorsers have an effect on brand awareness. Between two independent variables, the celebrity endorser has a stronger influence.